A differential current based protection scheme for DC microgrid - Giddalur, Eswaraiah; Laxmi, Askani Jaya (Institute of Advanced Engineering and Science, 2024)
A continuous increase in greenhouse emissions has led to more frequent use of renewable energy resources. The increased emergence of DC loads in day-to-day lives has further led to conversion to DC distribution lines. In prospect of getting more environmentally friendly, economical, and reliable power delivery a DC micro grid was developed and has become more common in recent years. The disaster management cell located at the Department of Electrical and Electronics Engineering has designed a DC micro grid which consists of sources provided from the grid, a battery bank, and an array of solar cells supplying to a set of nine loads, which are segregated into three sets of three loads each. This paper presents a protection scheme for the buses present in a micro grid that is based on the differential current principle. It is done with the help of a centralized protection controller that enables fault identification and fault isolation. This protection scheme is further extended to a DC ring-bus micro grid, where the centralized protection controller enables fault identification, fault location, and fault isolation. MATLAB/Simulink is used to obtain the simulation and verify the results.